2019
DOI: 10.1055/a-1014-2766
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Ultrasound Features Associated with Malignancy and Aggressiveness of Nonhypovascular Solid Pancreatic Lesions: Results from a Prospective Observational Study

Abstract: Background and Study Aims On contrast-enhanced imaging studies, nonhypovascular (i. e., isovascular and hypervascular) patterns can be observed in solid pancreatic lesions (SPLs) of different nature, prognosis, and management. We aimed to identify endoscopic ultrasound (EUS) features of nonhypovascular SPLs associated with malignancy/aggressiveness. The secondary aims were EUS tissue acquisition (EUS-TA) outcome and safety in this setting of patients. Patients and Methods This prospective observation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 34 publications
0
21
0
Order By: Relevance
“…Recent studies have suggested alternate methods to increase diagnostic yield. In particular, contrast-enhanced EUS could be of significant benefit in characterizing pancreatic lesions[ 6 ], and touch-imprint cytology allows for processing of a single specimen for both cytology and histology[ 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have suggested alternate methods to increase diagnostic yield. In particular, contrast-enhanced EUS could be of significant benefit in characterizing pancreatic lesions[ 6 ], and touch-imprint cytology allows for processing of a single specimen for both cytology and histology[ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, several factors can limit the sensitivity of EUS-FNA. EUS-FNA samples are typically processed as cytology, which does not allow for preservation of tissue architecture necessary for diagnosis of diseases such as gastrointestinal stromal tumor (GIST)[ 3 ], lymphoma[ 4 ], autoimmune pancreatitis[ 5 ], and pancreatic lesions with non-hypovascular contrast-enhancement pattern on EUS[ 6 ]. The diagnostic yield of EUS-FNA may be further compromised by the limited availability of on-site cytopathologists[ 7 - 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…The tip of the instrument is covered with a water-filled balloon allowing adequate transmission of ultrasound to improve image quality. A view of the whole pancreas is then taken according to the standard method of execution including a description of tumor location, size, margins (smooth or irregular), assessment of the echogenicity, distance from main pancreatic duct (MPD), evidence of upstream MPD dilatation, and vascular involvement [33,43]. PanNENs typically appear as hypoechoic, well-demarcated, round, hypervascular, homogeneous internal echo pattern lesions.…”
Section: Eus Technique and B-mode Evaluationmentioning
confidence: 99%
“…The majority of PanNENs are solid lesions but less commonly may also appear as cystic [12,32,33,45]. However, lesions with diameter >2 cm, irregular margins, heterogeneous echotexture, and upstream dilation of the MPD are significantly associated with malignancy/aggressiveness completely indistinguishable from the most common adenocarcinoma [12,43,44]. In addition, because some patients may present multiple PanNENs, (MEN in 36% to 81%) [42] it is important to examine the entire pancreas to exclude synchronous lesions, and if present, awareness of suspicious features may help the endosonographer to choose the lesion to be punctured, [12,32,33,42].…”
Section: Eus Technique and B-mode Evaluationmentioning
confidence: 99%
“…Endosonographic characteristics of malignant lymph nodes include a large size, hypoechogenicity, distinct border, round shape, and high tissue stiffness on elastography [ 3 , 4 ]. Unfortunately, simple LN morphology assessed through EUS is not sufficient to definitively distinguish benign nodes from malignant ones, thus an appropriate tissue sampling-aimed technique with concomitant pathological confirmation is often employed [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%